Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12889-020-08964-3
|View full text |Cite|
|
Sign up to set email alerts
|

Stigma for common mental disorders in racial minorities and majorities a systematic review and meta-analysis

Abstract: Background There is a strong stigma attached to mental disorders preventing those affected from getting psychological help. The consequences of stigma are worse for racial and/or ethnic minorities compared to racial and/or ethnic majorities since the former often experience other social adversities such as poverty and discrimination within policies and institutions. This is the first systematic review and meta-analysis summarizing the evidence on the impact of differences in mental illness stigma between racia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(79 citation statements)
references
References 70 publications
0
64
0
1
Order By: Relevance
“…There is a clear sense of athletes accepting each other and being there for each other during such times. Athletes tend to get much more comfortable talking about it to each other rather than seeking professional help and very often that is where the mistake lies (30) . It is critical to understand that mental health related issues can be handled only by a qualified psychologist (25) .…”
Section: Resultsmentioning
confidence: 99%
“…There is a clear sense of athletes accepting each other and being there for each other during such times. Athletes tend to get much more comfortable talking about it to each other rather than seeking professional help and very often that is where the mistake lies (30) . It is critical to understand that mental health related issues can be handled only by a qualified psychologist (25) .…”
Section: Resultsmentioning
confidence: 99%
“…Each of these challenges may be exacerbated by the circumstances of the pandemic. A systematic review and meta-analysis showed that members of many minority communities express more stigma associated with seeking mental health support than members of majority communities ( Eylem et al., 2020 ). When combined with other social adversities, stigma may make minority women even less likely to seek help.…”
Section: How the Covid-19 Pandemic Has Affected Mental Health Of The mentioning
confidence: 99%
“…En el caso de la Facultad de Ciencias Médicas de la Universidad Nacional de Asunción, los servicios de salud mental ofrecidos para los estudiantes carecen de foco específico en el manejo de grupos minoritarios de la población (por ejemplo, población LGBTQ+, minorías étnicas). Más investigación debería examinar esto, con el fin de adaptar los servicios de salud mental a las necesidades específicas de los estudiantes pertenecientes a grupos minoritarios que experimentan problemas de salud mental (34).…”
Section: Discusionunclassified